Diffuse spinal cord astrocytoma in a pediatric patient with progressive quadriplegia of six years' duration: case report. - M.E.,, Aranda Calvillo; F.S.,, López Juárez; M.,, Laureano Rivera; M.,, Laureano Rivera; S.N.,, Hernández Pinales; J.A.,, Morlett Chávez; A.C., Cepeda-Nieto (Revista de Ciencias Médicas Torreón, 2025)
An unusual presentation of a diffuse astrocytoma in a pediatric patient is described. Astrocytomas are a group of primary intracranial neoplasms of the central nervous system. These tumors are characterized by a slow growth pattern, heterogeneous clinical manifestations, and multiple factors influencing their prognosis.The case of a 13-year-old female patient is discussed, with a six-year history of progressive quadriplegia and neurological symptoms. An MRI performed upon admission identified an intramedullary mass with both cystic and solid components, along with fusiform vasogenic edema at the cervical level (C2 to C8), which widened the spinal canal to a diameter of 3 centimeters. A surgical approach was undertaken to remove a 5 x 3 cm tumor. Histopathological analysis identified the tumor as a grade II diffuse astrocytoma, according to the 2021 World Health Organization classification.
Keywords: diffuse spinal cord astrocytmoa; primary spinal cord tumors; glioma